URGENSI DAN SISTEM PERTANGGUNGJAWABAN PIDANA KORPORASI SEBAGAI PELAKU TINDAK PIDANA KORUPSI - Ade Mahmud (Universitas Suryakancana, 2022)
The issue of criminal liability for corporations continues to be a concern for academics, practitioners and the business world because it always invites problems about who should be responsible for acts of corruption involving corporations. This study aims to analyze the urgency of corporate responsibility as perpetrators of corruption and the system of corporate responsibility in corruption. This study uses a normative juridical approach with secondary data analyzed descriptively qualitatively The results of the study show that the criminal liability of corporations as perpetrators of criminal acts of corruption is legally absolute as long as it can be proven that the act was intended for the benefit of the corporation, meaning that the actus reus mens rea in the management is considered as the evil intention of the corporation so that the corporation is very relevant to be burdened with criminal responsibility. The corporate criminal responsibility system which is considered appropriate for corruption is a responsibility system that places the corporation as the maker of the corporation that must be responsible even though in fact the act was carried out by the management but the action is seen as a corporate action.Keywords: Corruption, Corporate Liability.